THE INFLUENCE OF BRAND KNOWLEDGE OF CELEBRITY ENDORSER AND PRODUCT TO BRAND KNOWLEDGE TRANSFER A CASE STUDY ON TELKOMFLEXI - ANINDHITA (NIM : 29107005), SHINTA
TelkomFlexi is a CDMA-based product of PT Telkom Tbk. with advanced technology. Initially, TelkomFlexi only signed The Changcuters, a Bandung-based band to be the endorser. Afterwards, this CDMA provider decided to add another endorser, Kirana Larasati, a young selebriti who was frequently seen on soap operas. By conducting a measurement on the level of brand knowledge among Kirana Larasati and TelkomFlexi, it is expected to be known that whether Kirana is actually able to increase the awareness on TelkomFlexi and has perfectly suited with the wanted image. The objectives of this research is to analyze the dimensions of brand knowledge from Kirana Larasati and TelkomFlexi, also the level of brand knowledge transfer which occurred among them. Data were collected through questionnaires sent to 300 customers of TelkomFlexi in Bandung aged 17-40 years old and have been subscribing less than a year. Data were analyzed using path analysis, through regression method. The result showed that the brand knowledge transfer between Kirana Larasati and TelkomFlexi had a significant, simultaneous influence from the brand knowledge of both entities. However, with the level of significance (Sig.) 0.854, brand knowledge of TelkomFlexi did not have that much influence to the transfer compared to Kirana‟s, if counted simultaneously. Alongside path analysis and regression, this research also collected qualitative data in the form of interviews with the Corporate Communications and Consumer divisions‟ staff of PT Telkom Tbk., and 112 respondents. The result showed that Kirana Larasati was chosen based on the spur-of-the-moment popularity, supported by the unsatisfying performance of The Changcuters, migration of frequencies, and the Ã‚Â“youthÃ‚Â” program of TelkomFlexi and PT Telkom Tbk. Based on these results, it is expected that TelkomFlexi would have more wisdom and be more careful in determining endorsers for the product. Research on endorsers should be conducted within the frame of the endorsers‟ long-term values, by estimating how they would develop in the future based on their potential and not only because they were famous at a certain time.